Dynamic warmup routines for sports - Faccioni, A.
The alternative warm-up procedures that I am suggesting is a variation of the above traditional method. With more active jogging and dynamic stretching techniques, the athlete will be better prepared for the ensuring session or game. In training situations the athlete will spend less time in the warm-up phase therefore allowing more time for the main body of the session where all the learning takes place.